1989
DOI: 10.1002/jlb.45.5.416
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Monokine Gene Expression: Prostaglandin E2 Suppresses Tumor Necrosis Factor but Not Interleukin-1α or β-mRNA and Cell-Associated Bioactivity

Abstract: Prostaglandin E2 (PGE2)-mediated suppression of macrophage interleukin-1 alpha,beta and tumor necrosis factor-alpha synthesis was examined at the cellular and molecular levels. Treatment of lipopolysaccharide (LPS)-stimulated adjuvant-elicited murine macrophages with 5 x 10(-7) M PGE2 caused a 70% reduction in cell-associated TNF but had no suppressive effect on cell-associated interleukin-1 (IL-1) activity. Consistent with this result, Northern blot and nuclear transcription analyses demonstrated suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
4

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 0 publications
6
49
0
4
Order By: Relevance
“…This finding was unexpected based on previous evidence that both IL-6 and TNF-a are typically regulated by the same transcription factor, NF-kB. 35 While not tested here, AngII has been shown to promote prostaglandin production, in particular prostaglandin E2 (PGE2), which in turn has been shown to inhibit the production of TNF-a while enhancing IL-6 production, thus supporting our findings 36,37 The pro-inflammatory nature of IL-6 is supported by evidence that the expression of IL-1, a well-known pro-inflammatory cytokine, was also upregulated by AngII exposure. 38 In summary, we provide evidence that there is variable expression of AT 1 R in subsets of purified monocytes, with greater expression seen in CD14 + /CD16 + monocytes.…”
Section: Mediasupporting
confidence: 80%
“…This finding was unexpected based on previous evidence that both IL-6 and TNF-a are typically regulated by the same transcription factor, NF-kB. 35 While not tested here, AngII has been shown to promote prostaglandin production, in particular prostaglandin E2 (PGE2), which in turn has been shown to inhibit the production of TNF-a while enhancing IL-6 production, thus supporting our findings 36,37 The pro-inflammatory nature of IL-6 is supported by evidence that the expression of IL-1, a well-known pro-inflammatory cytokine, was also upregulated by AngII exposure. 38 In summary, we provide evidence that there is variable expression of AT 1 R in subsets of purified monocytes, with greater expression seen in CD14 + /CD16 + monocytes.…”
Section: Mediasupporting
confidence: 80%
“…For example, PGE 2 inhibits expression of MHC class II proteins (8) and thus may interfere with antigen-presenting functions of the macrophage. Cytokine production is likewise inhibited by PGE 2 (6,7). Our studies have demonstrated that the actions of PGE 2 to suppress cytokine production by macrophages are mediated almost exclusively by the EP4 receptor; PGE 2 has no effect on LPS-stimulated cytokine release in EP4-deficient macrophages.…”
Section: Figurementioning
confidence: 56%
“…9). PG-mediated regulation of myeloid TNF production was reported (63,64). We presented only TNF-a release, but other inflammatory mediators might be modulated.…”
Section: Discussionmentioning
confidence: 89%